2012
DOI: 10.1016/j.clim.2011.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HLA DR epitope de-immunization of Factor VIII in vitro and in vivo

Abstract: T cell-dependent development of anti-factor VIII (FVIII) antibodies that neutralize FVIII activity is a major obstacle to replacement therapy in hemophilia A. To create a less immunogenic therapeutic protein, recombinant FVIII can be modified to reduce HLA binding of epitopes based on predicted anchoring residues. Here, we used immunoinformatics tools to identify C2 domain HLA DR epitopes and predict site-specific mutations that reduce immunogenicity. Epitope peptides corresponding to original and modified seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 48 publications
0
65
0
Order By: Relevance
“…Evaluating T-cell activation with peptides alone is useful for showing that a known epitope is abolished (20), but it is insufficient for demonstrating that new epitopes have not been created. For instance, mutations could alter antigen processing of the protein and potentially generate new epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating T-cell activation with peptides alone is useful for showing that a known epitope is abolished (20), but it is insufficient for demonstrating that new epitopes have not been created. For instance, mutations could alter antigen processing of the protein and potentially generate new epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + T-cell support is initiated by antigen-presenting cells (APCs), which display peptide fragments derived from foreign proteins on MHC class II molecules that bind T-cell receptors (14,15). Several studies have identified human-specific T-cell epitopes in therapeutic proteins (16)(17)(18), and in some cases proteins were produced by mutating amino acids within the protein and were shown to be less immunogenic using mouse models (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…First, the lower the intrinsic immunogenicity of a second FVIII product, the greater the probability of not breaking tolerance to epitopes shared between products. 40 Second, the host could be conditioned to mount a tolerogenic response on receiving the new product in the form of a negative vaccination strategy. 41 From a theoretical, immunologic point of view, the claim of safety issues on switching from a plasma-derived product to a molecularly defined bioengineered one, or on changing biodrug, appears to be weak.…”
Section: Immunogenicity Considerations Related To Switchingmentioning
confidence: 99%
“…23 Moise et al used computational prediction, HLA-DR peptide binding assays, and immunizations of HLA-DRA*01-DRB1*03:01 and -DRB1*04:01 transgenic mice to identify 6 immunogenic peptides in the FVIII-C2 domain. 24 Van Haren et al investigated naturally processed FVIII peptides by sequencing peptides eluted from HLA-DR on dendritic cells isolated from HLA-DRB1-typed donors. 25,26 These studies identified 6 to 18 FVIII core peptides per individual that could potentially be recognized by their T cells.…”
Section: Introductionmentioning
confidence: 99%